Neoplastic fistula treatment esoph ago-tracheo-bronchial by transtumoral endosophageal tubes - Peryroulou, Alfredo; Bergalli, Luis; Soto, Juan P.; Priario, Julio C.; Pradines, Jorge C. (Cirugía del Uruguay, 1978)
Respiratory esophageal fistulas are a frequent complication in the evolution of cancer of middle and upper third of esophagus. This incurable condition carries with it a painful survival. From the numerous paliative procedures suggested, the authors have selected transtumor intubation by means of tubes put in place by the use of traction. Experience is scant (6 cases) as compared with other foreign series, but results have been truly encouraging. Some clinical cases are presented and these show that it is an acceptable method for the treatment of malign esophago-respiratory ulcers.